Analisis Pengelolaan Dana Hibah Kepada Polri Di Kota Jayapura Tahun 2022: (Studi Kasus Batalyon A Pelopor - Sat Brimob Polda Papua) - Duwith, Clief; Marlissa, Elsyan R.; Hutajulu, Halomoan (Universitas Cenderawasih, 2023)
Grant aid expenditure is one of the expenditure accounts in the Regional Revenue and Expenditure Budget (APBD) which attracts public attention and often becomes the headline in the mass media. This is because there are many parties who need this grant assistance and there are many interests that can be accommodated, both for the welfare of society and certain political interests. Based on the principle of decentralization, regional governments regulate and manage government affairs which fall under regional authority in the system of the Unitary State of the Republic of Indonesia. Regional governments, to be able to carry out government affairs which fall under their authority, are given financial powers in the context of funding government affairs which fall under regional authority (Law No. 32 of 2004). Presidential Decree No. 74 of 2001 concerning Procedures for Supervising the Implementation of Regional Government, Article (16) states that regional government supervision is an activity process aimed at ensuring that regional government runs in accordance with plans and provisions of applicable laws and regulations. The aim of providing grants is to maintain public security and order; enforce the law; as well as providing protection, guidance and services to the community in order to maintain domestic security and order.